2014
DOI: 10.1159/000362622
|View full text |Cite
|
Sign up to set email alerts
|

Intraperitoneal Interleukin-6 Levels Predict Peritoneal Solute Transport Rate: A Prospective Cohort Study

Abstract: Background: To evaluate the association of dialysate interleukin-6 (IL-6), a marker of ongoing peritoneal inflammation, with the alteration of peritoneal solute transport rate (PSTR) in continuous ambulatory peritoneal dialysis (CAPD) patients. Methods: Stable CAPD patients were enrolled in the present study. A total of 128 patients were analyzed in this prospective study. IL-6 concentration in the overnight effluent was determined and expressed as the IL-6 appearance rate (IL-6AR). Mass transfer area coeffici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
24
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 67 publications
3
24
0
2
Order By: Relevance
“…Local production of IL-6 is a marker of ongoing intraperitoneal inflammation in PD patients [24]. Similar to these findings, our previous prospective study has shown that dialysate IL-6AR had positive correlation with PD duration and peritoneal glucose exposure, while negatively correlated with urine output [25]. In this study, we found that patients in the high IL-6AR group were more likely to be male, anuric, and with a longer PD duration when compared with their counterparts in the low group.…”
Section: Discussionsupporting
confidence: 66%
“…Local production of IL-6 is a marker of ongoing intraperitoneal inflammation in PD patients [24]. Similar to these findings, our previous prospective study has shown that dialysate IL-6AR had positive correlation with PD duration and peritoneal glucose exposure, while negatively correlated with urine output [25]. In this study, we found that patients in the high IL-6AR group were more likely to be male, anuric, and with a longer PD duration when compared with their counterparts in the low group.…”
Section: Discussionsupporting
confidence: 66%
“…Pecoits‐Filho et al found that IL‐6 and sIL‐6R could be detected in PDF, and IL‐6 and sIL‐6R were both closely related to PSTR. Furthermore, our previous study reported that intraperitoneal IL‐6 levels could predict the alteration of PSTR during long‐term follow‐up . Kim NH et al reported that IL‐6 directly induced phosphorylation of JAK1/STAT3 to upregulate VEGF expression in HepG2 cells.…”
Section: Discussionmentioning
confidence: 95%
“…Interleukin‐6 (IL‐6) is a biomarker of ongoing intraperitoneal inflammation in PD patients . Our previous work and a recent large‐scale study showed that the intraperitoneal IL‐6 level is an independent risk factor and a strong predictor of increasing PSTR in PD patients . IL‐6 is multifunctional cytokine involved in the regulation of acute‐phase responses, hematopoiesis, cell regeneration and transition from innate to acquired immunity .…”
mentioning
confidence: 99%
“…Thus, high readings of inflammatory markers such as IL-6 or other cytokines are currently suggested as emerging biomarkers for (see table 1) but may require differential interpretations depending on the clinical context. 12,[22][23][24][25][26][27][28][29] Biomarker research in the context of Peritoneal Membrane Remodeling Currently, data on peritoneal transport characteristics from the peritoneal equilibration test (PET), and in particular their change over time, are used to guide PD patient treatment and management. The previously well-discussed candidate biomarker CA-125 was rapidly applied to estimate mesothelial cell mass as a surrogate parameter for the peritoneal membrane status in studies comparing different dialysis fluids (see table 1), although its utility in this context remains contentious.…”
Section: Biomarker Research In the Context Of Chronic Peritoneal Inflmentioning
confidence: 99%